Character Education Strategy through Entrepreneurship Approach in Integrated Islamic Schools (IT) - Ika Hartika; Lukmannulhaqim Lukmannulhaqim (Budapest International Research and Critics University, 2022)
It takes a strategy for proper character education for children in Integrated Islamic Schools (IT) by combining two different concepts, namely the concept of religion and the concept of economics. The combination of these two concepts is expected to be able to form a strategy that is considered appropriate for students. The combination of these concepts is expected to be able to form a strong character for children. The religious character is expected to increase faith and piety while the economic concept will build an entrepreneurial spirit in children from an early age. By using ANP, it is expected to be able to form an appropriate strategy in achieving the goals of character education. In determining the strategy it is necessary to identify the main problem then make a solution in answering the question and will produce an appropriate strategy. In achieving the right character education for children in integrated Islamic schools, synergy is needed between schools and families. This synergy will produce a pattern of character education that can be achieved in character education.